Achieving Excellence in Customer Relationship Management - Clark, Moira; McDonald, Malcolm; Smith, Brian (Cranfield University School of Management, 2002)
This report covers the work of the Cranfield CRM Research Formn for the first year of its operation Directed and funded by a group of organisations across many sectors, the goals of the Forum are to enable excellence in Customer Relationship Management (CRM) by defining and understanding this important management process.